Pemberdayaan Masyarakat Dalam Pemanfaatan Alokasi Dana (ADD) (Suatu Studi Di Desa Bukumatiti Kecamatan Jailolo Kabuapten Halmahera Barat) - BAURA, JULISKA; Mandey, Jantje; Tulusan, Femmy (Sam Ratulangi University, 2015)
ABSTRACT:The purpose of this study was to determine pemeberdayaan Community In Utilization VillageAllocation Fund (ADD) in the village of Bukumatiti the District Jailolo West Halmahera as the Regulation ofthe Minister of Home Affairs Number 113 2014 About the Financial Management of the Village in Article 2Paragraph 1 states that the financial management of the village should be based the principles oftransparency, accountability and participatory. To determine the Community Empowerment in Rural FundAllocation Utilization (ADD), the research method used was a qualitative descriptive study consists of 6research informants.Empowering communities in the utilization of the Village Fund Allocation (ADD) in the village ofBukumatiti has not been run in accordance with the principles of financial penegelolaan villages of theprinciples of transparency, accountability and participatory. Based on the results of field research on theutilization of public empowerment Village Fund Allocation (ADD) village government is not open to thepublic regarding the use of the Village Fund Allocation (ADD) so that people do not know how much the costdisbursed to community empowerment; there is no accountability in each realization of the program on thecommunity; as well as the village government as the financial manager of the Village Fund Allocation(ADD) partsispasi not involve the community in the form of decision-making, planning, implementation andthe evaluation of results.In society to use the Village Fund Allocation (ADD) in the hope the government village BukmatitiDistrict of Jailolo as a manager and executor of every activity that comes from the Village Fund Allocation(ADD) should be based on the principles of financial management of villages sebagimana contained inRegulation Home Affairs Number 113 2014 About the Financial Management of the Village in Article 2Paragraph 1 states that the financial management of the village should be based on the principles oftransparency, accountability, danpartisipatif.Keywords: Community Development, Utilization Village Fund Allocation.